Aging traits and sustainable trophy hunting of African lions. (September 2016) - Miller, Jennifer R.B.; Balme, Guy; Lindsey, Peter A.; Loveridge, Andrew J.; Becker, Matthew S.; Begg, Colleen; Brink, Henry; Dolrenry, Stephanie; Hunt, Jane E.; Jansson, Ingela; Macdonald, David W.; Mandisodza-Chikerema, Roseline L.; et al.
Abstract: Trophy hunting plays a significant role in wildlife conservation in some contexts in various parts of the world. Yet excessive hunting is contributing to species declines, especially for large carnivores. Simulation models suggest that sustainable hunting of African lions may be achieved by restricting offtakes to males old enough to have reared a cohort of offspring. We tested and expanded criteria for an age-based approach for sustainably regulating lion hunting. Using photos of 228 known-age males from ten sites across Africa, we measured change in ten phenotypic traits with age and found four age classes with distinct characteristics: 1–2.9 years, 3–4.9 years, 5–6.9 years, and ≥ 7 years. We tested the aging accuracy of professional hunters and inexperienced observers before and after training on aging. Before training, hunters accurately aged more lion photos (63%) than inexperienced observers (48%); after training, both groups improved (67–69%). Hunters overestimated 22% of lions < 5 years as 5–6.9 years (unsustainable) but only 4% of lions < 5 years as ≥ 7 years (sustainable). Due to the lower aging error for males ≥ 7 years, we recommend 7 years as a practical minimum age for hunting male lions. Results indicate that age-based hunting is feasible for sustainably managing threatened and economically significant species such as the lion, but must be guided by rigorous training, strict monitoring of compliance and error, and conservative quotas. Our study furthermore demonstrates methods for identifying traits to age individuals, information that is critical for estimating demographic parameters underlying management and conservation of age-structured species. Graphical abstract: Highlights: Age-based methods to sustainably hunt require precise age estimates from appearance. Used photos to track trait change with male lion age and test hunter aging accuracy. 6 traits precisely indicate 4 age classes: 1–2.9 year, 3–4.9 year, 5–6.9 year, ≥ 7 year. Hunters used traits to accurately age 69% of lions, with fewest errors for ≥ 7 year. Min harvest age of 7 year with strict enforcement could enable sustainable harvest.